Hybrid biobased recyclable epoxy composites for mass production. (14th September 2017) - Cicala, G.; Mannino, S.; La Rosa, A.D.; Banatao, D.R.; Pastine, S.J.; Kosinski, S.T.; Scarpa, F.
Abstract : Hybrid flax/carbon composites were studied in this artcle. The matrix used was developed using a sustainable green epoxy monomer cured by a novel cleavable amine. The combination of cleavable amine with green epoxy monomers led to a fully recyclable composite. The laminates were manufactured by using High Pressure Resin Transfer Molding with injection cycles down to 25 sec and cure cycles of 8 min at 120°C, followed by postcuring at 120°C for 1 h. The effect of the stacking sequence of the laminates was analyzed in terms of the tensile, flexural, and impact properties. A chemical recycling was also performed and the mechanical properties of the recovered thermoplastic measured. POLYM. COMPOS., 39:E2217–E2225, 2018. © 2017 Society of Plastics Engineers